Quantification of emigration and habitat use inform stocking rates of lake sturgeon (Acipenser fulvescens, Rafinesque, 1817) in the Cumberland River, Tennessee, USA. (12th December 2017) - Ganus, J. E.; Mullen, D. M.; Miller, B. T.; Cobb, V. A.
Summary: Whereas lake sturgeon Acipenser fulvescens stocking began in the Cumberland River system in 2006, reservoir‐specific data are needed to assess restoration efforts as well as provide information to support sturgeon management decisions. The purpose of this study was to (i) assess dam passage and emigration rates of tagged hatchery‐reared juvenile lake sturgeon through the Cheatham and Old Hickory locks and dams, (ii) estimate reservoir section use and movement by tagged hatchery‐reared juvenile lake sturgeon within Cheatham Reservoir, and (iii) estimate the minimum annual stocking rate for Cheatham Reservoir from model parameters. To quantify emigration from Cheatham Reservoir, hatchery‐raised juvenile lake sturgeon were surgically implanted with acoustic transmitters and passively tracked with archival submersible ultrasonic receivers. Annual section usage was estimated by actively tracking juvenile lake sturgeon at a minimum of once quarterly. Matrix projection models were used to create simple life tables from demographic data (age specific mortality, growth and fecundity), varying emigration rates (0.0, 0.01, and 0.10) and spawning fractions (0.10, 0.15 and 0.20) to estimate the annual stocking rate necessary to achieve an adult population of 750 individuals after 40 years. Percent downstream passage of tagged lake sturgeon through Cheatham Lock and Dam (CLD) was 32% ( n  = 11) in 2011 and 9% ( n  = 3) in 2012. Percent upstream passage of tagged lake sturgeon through Old Hickory Lock and Dam (OHLD) was 32% ( n  = 11) in 2011 and 28% ( n  = 9) in 2012. The total emigration rate for Cheatham Lake was 65% in 2011 and 38% in 2012. Upstream movement was high for each cohort as 75% ( n  = 25) in 2011 and 81% ( n  = 26) in 2012 of tagged lake sturgeon that moved upstream to a position just below OHLD within five days post‐stocking. Average upstream distance traveled post‐stocking in 2011 was 25.2 river km (rkm), and downstream 3.6 rkm. Average upstream distance traveled in 2012 post‐stocking was 35.6 rkm, and downstream 16.1 rkm. The estimated minimum annual stocking rates would be 1, 770, 2, 456 and 48, 778 at 0%, 1% and 10% emigration rates when applied equally over 40 years of stocking.